2015
DOI: 10.1074/jbc.m115.655688
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Stimulate the Level of the σ38 Subunit (RpoS) of Escherichia coli RNA Polymerase, Resulting in the Induction of the Glutamate Decarboxylase-dependent Acid Response System via the gadE Regulon

Abstract: Background: Polyamines are ubiquitous compounds present in most organisms. Results: Polyamines increase the level of RpoS, the 38 -RNA-polymerase subunit, even in non-amber-strain, to induce glutamate-dependent-acid resistance (GDAR) in Escherichia coli via gadE. Conclusion: GDAR activation by polyamines is the indirect effect of increased RpoS level. Significance: Polyamines are not only important for acid survival, but polyamine-dependent increase in RpoS levels will have pleiotropic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…promoter region, which is known to be highly RpoS dependent and has been used by others as reporter of RpoS activity (57)(58)(59). A microscopic analysis of stationary-phase cultures grown at 37°C revealed that all strains showed significant GFP expression, with the exception of the BW25113⌬rpoS mutant strain, which showed no detectable fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…promoter region, which is known to be highly RpoS dependent and has been used by others as reporter of RpoS activity (57)(58)(59). A microscopic analysis of stationary-phase cultures grown at 37°C revealed that all strains showed significant GFP expression, with the exception of the BW25113⌬rpoS mutant strain, which showed no detectable fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Polyamines stimulate synthesis of specific proteins in E. coli cells through mRNA transcription and stabilizing various RNA‐RNA interactions (Chattopadhyay et al . ; Igarashi & Kashiwagi ). It is possible that some long and branched polyamines are involved in regulating the expression of certain proteins.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the enhanced agmatine production caused by organic acids may be associated with the mechanism of resistance to acidic environments, resembling the bacterial acid resistance system involving amino acid decarboxylation (39). During E. coli exposure to an acidic environment, a series of PLP-dependent decarboxylases (e.g., GadA/B and AdiA) decarboxylate glutamic acid and arginine to form GABA and agmatine, respectively, with a concomitant consumption of an intracellular proton (39)(40)(41). This contributes to the homeostatic maintenance of the cytoplasmic pH (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%